Risk Management in The Packaging Unit at Animal Feed Industry Sidoarjo, Indonesia - Hasnur Zalsabila Arna; Cempaka Puspita Siwi; Y. Denny A. Wahyudiono (Universitas Airlangga, 2023)
Introduction: Animal feed industry Sidoarjo is one of the companies in the animal feed manufacturing industry. The packaging unit is the last unit in the production process that packs the feed ingredients and arranges the finished goods. A location with the most safety hazards based on the work accident reports for 2010-2017 is in the packaging unit as many as 15.78%. The purpose of this research is to analyze the risk management of work safety in the packaging unit of animal feed industry Sidoarjo. Methods: Based on the data collection method, this research was included in observational research with a cross-sectional design. The subjects in this research were workers (37 people) in the animal feed packaging and the Health Safety Environment (HSE) units. The research was conducted at the packaging unit of Animaal Feed Industry, Sidoarjo, Indonesia in November 2019-June 2020. Results: Based on hazard identification, there were 15 hazards with a risk analysis of 53% moderate risk and 47% high risk. The risk evaluation obtained was including 53% tolerable risk and 47% intolerable risk. After controlling efforts, there was a decrease in the risk category. Conclusion: The residual risk obtained after controlling carried out experienced a reduction of moderate risk by 100% and high risk by 71%. The remaining risk was 33% moderate risk and 13% high risk.